Carbohydrate ingestion improves oxygen delivery in acute hypoxia - Golja, P.; Flander, P.; Klemenc, M.; Maver, J.; Princi, T. (High Altitude Medicine & Biology, 2008)
It is generally accepted that an increase in blood CO2 increases ventilation. We also know that during carbohydrate metabolism a larger amount of CO2 is produced than during metabolism of lipids or proteins. The aim of the present study was therefore to assess whether carbohydrate ingestion can increase CO2 production enough to stimulate ventilation, which could in turn increase arterial oxygenation and alleviate the symptoms of hypoxia in a hypoxic environment. Fourteen subjects participated in two trials, which consisted of two normoxic and an acute hypoxic period (FiO2 = 12.86%). Following the first control normoxic period, the subjects ingested either a 10% water solution of sucrose (CHO; 4 kcal/kg body mass) or an equal volume of water (control). Hemoglobin saturation, heart rate, and ventilation parameters were monitored throughout the experiment. In contrast to the control trial, CO2 production (VCO2; L), ventilation (V; L/min), and heart rate were all significantly (p < 0.001) increased in the CHO trial during the second normoxic exposure; these parameters were also significantly elevated during the hypoxic exposure, as compared to the control trial. Carbohydrate ingestion 40 min prior to acute hypoxic exposure significantly (p < 0.001) improved hemoglobin saturation by 4%. The results suggest that ingestion of carbohydrates can improve arterial oxygenation during acute hypoxic exposure.